Beet pulp as soluble fiber source and dietary energy levels for growing pigs under heat stress - Choi, Yo Han; Min, Ye Jin; Jeon, Da Yeon; Jin, Hyun Ju; Jeong, Yong Dae; Park, Hyun Ju; Hosseindoust, Abdolreza; Ha, Sang Hun; Mun, Jun Young; Kim, Jin Soo; Kim, Jo Eun (Journal of animal science and technology, 2023)
The study evaluated the effects of dietary fiber and energy levels administered during two growing periods (d 0-28 and d 29-56) for pigs exposed to a high temperature. A total of 96 growing pigs were used in six treatments as: Two treatments in thermoneutral temperature (21°C-24°C) with dietary energy of 3,300 and the inclusion of high or low fiber, two treatments in heat stress (30°C-34°C) with dietary energy of 3,300 and the inclusion of high or low fiber, and two treatments in heat stress with dietary energy of 3,450 and the inclusion of high or low fiber. Among standard energy level treatments, heat-stressed pigs showed lower average daily gain (ADG), feed intake, digestibility of dry matter, gross energy, crude protein, and crude fiber in phases 1 and 2. Moreover, higher concentrations of acetate, propionate, butyrate, and total short-chain fatty acid (SCFA) in feces were shown in pigs fed high fiber diets. There was a negative interaction between dietary fiber and energy for the fecal concentration of isobutyrate in phase 1 and valerate in phase 2. Pigs in heat stress treatments showed a higher rectal temperature, respiratory rate, hair cortisol, plasma zonulin, and fecal lipocalin-2. Among heat stress treatments, the overall ADG was increased in pigs fed high fiber. Pigs fed high dietary fiber showed a greater concentration of acetate, propionate, butyrate, and total SCFA. High fiber treatments decreased plasma zonulin. In conclusion, the inclusion of beet pulp, soluble fiber, at the level of 4% looks necessary in pigs diet during heat stress.The study evaluated the effects of dietary fiber and energy levels administered during two growing periods (d 0-28 and d 29-56) for pigs exposed to a high temperature. A total of 96 growing pigs were used in six treatments as: Two treatments in thermoneutral temperature (21°C-24°C) with dietary energy of 3,300 and the inclusion of high or low fiber, two treatments in heat stress (30°C-34°C) with dietary energy of 3,300 and the inclusion of high or low fiber, and two treatments in heat stress with dietary energy of 3,450 and the inclusion of high or low fiber. Among standard energy level treatments, heat-stressed pigs showed lower average daily gain (ADG), feed intake, digestibility of dry matter, gross energy, crude protein, and crude fiber in phases 1 and 2. Moreover, higher concentrations of acetate, propionate, butyrate, and total short-chain fatty acid (SCFA) in feces were shown in pigs fed high fiber diets. There was a negative interaction between dietary fiber and energy for the fecal concentration of isobutyrate in phase 1 and valerate in phase 2. Pigs in heat stress treatments showed a higher rectal temperature, respiratory rate, hair cortisol, plasma zonulin, and fecal lipocalin-2. Among heat stress treatments, the overall ADG was increased in pigs fed high fiber. Pigs fed high dietary fiber showed a greater concentration of acetate, propionate, butyrate, and total SCFA. High fiber treatments decreased plasma zonulin. In conclusion, the inclusion of beet pulp, soluble fiber, at the level of 4% looks necessary in pigs diet during heat stress.